A pilot study on acupuncture for lower urinary tract symptoms related to chronic prostatitis/chronic pelvic pain - Stone Brian A; Samadi David; Bemis Debra L; Jin Zhezhen; Capodice Jillian L; Kapan Steven; Katz Aaron E (BMC, 2007)
Abstract Background The etiology and treatment of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) remain poorly understood. Pain, lower urinary tract voiding symptoms and negative impact on quality of life (QOL) are the most common complaints. Acupuncture, which has been widely used to treat painful and chronic conditions, may be a potential treatment to alleviate the constellation of symptoms experienced by men with CP/CPPS. The purpose of our study was to assess the impact of standardized full body and auricular acupuncture in men refractory to conventional therapies and collect pilot data to warrant further randomized trials. Methods Ten men diagnosed with category IIIA or IIIB CP/CPPS >6 months, refractory to at least 1 conventional therapy (antibiotics, anti-inflammatory agents, 5-α reductase inhibitors, α-1 blockers) and scoring >4 on the pain subset of the NIH-CPSI were prospectively analyzed in an Institutional Review Board (IRB) approved, single-center clinical trial (Columbia University Medical Center IRB#AAAA-7460). Standardized full body and auricular acupuncture treatment was given twice weekly for 6 weeks. The primary endpoints were total score of the NIH-CPSI and assessment of serious adverse events. The secondary endpoints were individual scores of the NIH-CPSI and QOL questionnaire scores of the short-form 36 (SF-36). Results The median age of the subjects was 36 years (range 29-63). Decreases in total NIH-CPSI scores (mean ± SD) after 3 and 6 weeks from baseline (25.1 ± 6.6) were 17.6 ± 5.7 (P < 0.006) and 8.8 ± 6.2 (P < 0.006) respectively and remained significant after an additional 6 weeks of follow-up (P < 0.006). Symptom and QOL/NIH-CPSI sub-scores were also significant (P < 0.002 and P < 0.002 respectively). Significance in 6 of 8 categories of the SF-36 including bodily pain (P < 0.002) was achieved. One regression in the SF-36 vitality category was observed after follow-up. There were no adverse events. Conclusion The preliminary findings, although limited, suggest the potential therapeutic role of acupuncture in the treatment of CP/CPPS. Data from this and previous studies warrant randomized trials of acupuncture for CP/CPPS and particular attention towards acupuncture point selection, treatment intervention, and durability of acupuncture.